Tetra-μ-acetato-κ(8) O:O′-bis{[2-(m-tolylamino)pyridine-κN]copper(II)} - Fairuz, Zainal Abidin (International Union of Crystallography, 2009)
In the crystal structure of the title compound, [Cu(2)(C(2)H(3)O(2))(4)(C(12)H(12)N(2))(2)], the binuclear molecule lies about a center of inversion; the four acetate groups each bridge a pair of Cu(II) atoms. The coordination of the metal atom is distorted square-pyramidal, with the bonding O atoms comprising a square basal plane and the coordinating N atom of the N-heterocycle occupying the apical position. The pyridine ring is twisted with respect to the benzene ring at a dihedral angle of 45.68 (16)°. Intramolecular N—H⋯O hydrogen bonding is present between the imino and carboxy groups.